From "Informant" to "Influencer": Reframing Research Language to Build Trust in Marginalized Communities. - Gonzalez, Amanda I. Aguila; Faseru, Babalola; Collie-Akers, Vicki; Ablah, Elizabeth (American Journal of Public Health, 2026)
The article discusses the need for inclusive language and culturally sensitive recruitment strategies to increase engagement with marginalized communities. It describes how terminology can facilitate or hinder engagement, trust, relationship building and information sharing in community-based social and behavioral health research. It explains the use of key informant interviews and some disadvantages of using the term "informant."